1986
DOI: 10.1128/aem.52.4.782-787.1986
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ammonium Oxidation by Nitrapyrin in Soil and Liquid Culture

Abstract: Inhibition of growth of axenic cultures of Nitrosomonas europaea by nitrapyrin was investigated in liquid culture and in soil. In liquid culture, exponentially growing cells were more sensitive than stationary-phase cells, possibly due to a requirement for uptake of nitrapyrin, metabolism of nitrapyrin, or both before inhibition. Differences in sensitivity were observed between the parent strain and two strains, spi and sp2, that were selected through repeated subculturing. These differences were reflected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…There are various nitrification inhibitors available, and some of them have been used in soil management over years in several countries (Trenkel, 1997;Di & Cameron, 2005;Moir et al, 2007;Singh & Verma, 2007). The inhibitory effect of the selected six reagents has been mainly explored on AOB or in some cases also on AOA enrichment cultures (Hooper & Terry, 1973;Powell & Prosser, 1986;Amberger, 1989;Zacherl & Amberger, 1990;Hatzenpichler et al, 2008;Jung et al, 2011;Kim et al, 2012;Mosier et al, 2012a).…”
Section: Resultsmentioning
confidence: 99%
“…There are various nitrification inhibitors available, and some of them have been used in soil management over years in several countries (Trenkel, 1997;Di & Cameron, 2005;Moir et al, 2007;Singh & Verma, 2007). The inhibitory effect of the selected six reagents has been mainly explored on AOB or in some cases also on AOA enrichment cultures (Hooper & Terry, 1973;Powell & Prosser, 1986;Amberger, 1989;Zacherl & Amberger, 1990;Hatzenpichler et al, 2008;Jung et al, 2011;Kim et al, 2012;Mosier et al, 2012a).…”
Section: Resultsmentioning
confidence: 99%
“…The betaproteobacterial AOB strains studied (Table 1) were grown in static liquid batch culture at 28 o C, as described by Keen & Prosser (1987) in modified Skinner and Walker medium (Powell & Prosser, 1986). All cultures were checked for heterotrophic bacterial contamination by plating on nutrient agar and by PCR amplification and denaturing gradient gel electrophoresis analysis.…”
Section: Bacterial Isolates and Growth Conditionsmentioning
confidence: 99%
“…A study of N. europaea biofilms reported that established biofilms were less inhibited by the nitrification inhibitor nitrapyrin and exhibited reduced growth rates compared to suspended cells (Powell and Prosser, 1992). Additionally, exponential cells of N. europaea exhibited greater inhibition of NH 3 oxidation when exposed to nitrapyrin compared to stationary-phase cultures (Powell and Prosser, 1986). A study of cadmium inhibition of N. europaea, based on O 2 uptake rates, demonstrated that cells in stationary phase were less inhibited over time than during exponential growth (Chandran and Love, 2008).…”
Section: Introductionmentioning
confidence: 99%